Harmonization formative in the design of interior spaces Hall of discussions in the design department (a model): بدريا محمد حسن فرج (Al-Academy, 2016)
Can not reach a comprehensive concept for interior design through the use of Harmonization term according transformations experienced by the terms of the variables associated with the backlog of cultures that characterize concepts according to the nature of the users of the spaces in the design output, which necessitates the meaning of the combination of knowledge, art, science, such as the type of perceptions design the Harmonization cognitive science with art to create products of the use of design configurations that help the designer to put such a product within the reality and like the fact that reliable, as well as the rational knowledge tend somehow to the objective specifically in facilitating the substance subject to perceptible on according to content and content design, note The interior design is based on the founding actors structure are the functional requirements, and the vision aesthetic, which depends Referents on different visions of the concepts of variety to produce vocabulary and configurations constituent differentiate its methods within the local technical capacity and cultures that impose the starting of which designs, so ensure Thread affordable four Brief chapters on according to research conditions, in the first chapter has been addressing the problem of research and justifications choice through goal setting and emphasize the importance that we listed in our class this with the reference in paragraph terminology to the Harmonization configuration, The second chapter was limited to the first two sections Harmonization formative eating, and the second topic dealt with design the spaces - discussions, and then the indicators that emerged from the researcher, while the third chapter research procedures in determining the sample through a process description and logical analysis, has been a researcher in the fourth quarter has sought to come up with results and conclusions in line with the content of the goal with the introduction of authorized sources, and in the What follows ask for some:- Characterized by the appearance of space design and content of the formative in terms of intellectual trends in the main space is divided into two principal two spaces: the first is intended for teachers and discussants supervisor professor and researcher, and the second is dedicated to attend through redundancy in the design layout.Involve the treating idea of Spaces and them Determinants on duplicates training depending on the nature of the design, which required so privacy design solutions